Elastic Plate Osteosynthesis of Long Bone Fractures usingVeterinary Cuttable Plates in Young Dogs - D, Sai Bhavani D; NVV, Hari Krishna; M, Sreenu; G Venkat Naidu (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Twelve dogs below one year of age presented with a history of forelimb or hindlimb lameness, suggestive of either radius or tibia fracture were selected to study the fracture stabilisation by Elastic Plate Osteosynthesis (EPO) technique using 2.0/2.7 mm Veterinary Cuttable Plate (VCP). The implants were selected according to body weight and bone size. Post-operatively, the dogs were evaluated by clinical, radiographical and lameness grading. Primary healing was observed in eight cases and secondary healing in four cases. Fracture healing was observed by 30th post-operative day in most of the cases. The dogs regained full limb functionality by 15-30 days post-surgery. All the animals regained normal return to weight bearing early (within one month) with excellent to good limb usage. Plate removal was done in all cases on 5-8 weeks post-surgery. No major post-operative complications were observed. To conclude, the VCP used was inexpensive and the EPO technique using VCP was useful for long bone fractures of young dogs making it suitable for use in Veterinary practice and the technique resulted in early weight bearing and good functional limb out come without any complications